Integrated paper surface treatment agent based on AKD and preparation method thereof

By using components such as AKD wax, dodecyldimethylbenzyl ammonium bromide and nanogold in paper surface treatment agents, the process flow is simplified, the cost is reduced, and the water resistance and surface strength of the paper is improved, solving the problems of operating failures and high costs in the prior art.

CN116536956BActive Publication Date: 2025-04-25EAST CHINA UNIV OF SCI & TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211526668.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-04-25
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

During the preparation process, existing paper surface treatment agents have operational failures such as paste mesh, blankets, sticky rollers and sticky cylinders, resulting in poor yield, complex raw materials, cumbersome process, and high cost, which limits large-scale production and promotion.

Method used

Using an integrated paper surface treatment agent based on AKD, the process is simplified and cost-reduced by adding dodecyldimethylbenzyl ammonium bromide to the system as the phase transfer catalyst and nanogold as the precious metal nanocatalyst.

Benefits of technology

On the premise of ensuring excellent water resistance of the paper, the surface printing strength of the product is significantly improved, reducing the hair loss, powder loss and adhesion of the paper in high humidity environments, shortening the maturation time, reducing the cost by 15-20%, and reducing the amount of additives by 50%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005208019580000081
    Figure GDA0005208019580000081
  • Figure GDA0005208019580000091
    Figure GDA0005208019580000091
Patent Text Reader

Abstract

The present invention relates to the technical field of C08F paper surface treatment agents, and more specifically, the present invention provides an integrated paper surface treatment agent based on AKD and a preparation method thereof. The present invention introduces additives such as phase transfer catalysts and precious metal catalysts into AKD wax, significantly improves the surface printing strength of paper products, shortens the aging time, can completely replace the use of sizing agents in the pulp, reduces AKD hydrolysis and loss, greatly improves the additive absorption rate of the paper pulp, and reduces the return water pollution, which not only maintains the excellent water resistance of the paper, but also reduces the environmental protection treatment cost. At the same time, a lot of additives are added less, which reduces the clogging and pollution of the additives to the filter screen and the felt cloth, prolongs the service life of the forming net and the felt cloth, and prolongs the cleaning cycle, providing a new strategy for preparing the integrated paper surface treatment agent and expanding the application range of the integrated paper surface treatment agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of C08F paper surface treatment agent, and more specifically, provides an integrated paper surface treatment agent based on AKD and a preparation method thereof. Background Art

[0002] Paper surface treatment agent is one of many papermaking chemicals. It is a new functional material that improves paper performance. It is a general term for additives used to improve paper performance, including surface sizing agents, surface paper strength enhancers, surface finishing agents, paper water repellent agents, and information paper agents. Paper surface treatment agents can be used to improve sizing effects (water resistance, writing adaptability, etc.), improve surface strength and wear resistance, and improve printing adaptability (ink transferability, print concentration, glossiness, etc.). Therefore, developing a simpler and more efficient method for preparing paper surface treatment agents has become one of the research hotspots for researchers in recent years.

[0003] At present, the traditional surface treatment process includes two steps: internal sizing and surface sizing. In these two steps, in addition to adding sizing agents, surface paper strength enhancers, surface finishing agents, and paper water repellent agents are also added. The above steps have the following problems: (1) During the dehydration process of the wire and press sections, the sizing agent is easily lost with the white water, which increases the degree of pollution of the paper machine system, easily causes paper defects and paper breaks, and is not conducive to white water recovery and recycling; (2) The amount of sizing agent used is large and the cost is high; (3) It is easy to cause operational failures such as wire sticking, felt sticking, roller sticking, and cylinder sticking, which is complicated and costly.

[0004] A Chinese invention patent with patent publication number CN110105500A discloses a method for preparing a super-hydrophobic paper surface treatment agent. In this patent disclosure, fluorine-containing acrylate monomers and vinyl hard monomers are introduced into the system, focusing on solving the problem of poor hydrophobicity of paper surface treatment agents in the prior art. However, an oily initiator is used in its solution. During the preparation process, operational failures such as web sticking, felt sticking, roller sticking, and cylinder sticking may occur, resulting in a poor yield of the paper surface treatment agent, limiting its large-scale production and promotion.

[0005] The Chinese invention patent with patent publication number CN107447593A discloses a fluorinated acrylate copolymer emulsion paper surface treatment agent and its preparation method and application. In this patent, the fluorinated acrylate monomer is used to interact with other components in the system to focus on improving the air permeability, softness and mechanical strength of corrugated paper. However, the raw materials of the paper surface treatment agent are complex, the preparation process has cumbersome steps, and has high requirements for process operation and long production time.

[0006] Integrated sizing technology is to complete sizing at one time directly through surface sizing. By using integrated sizing technology, a reasonable surface sizing process is controlled. Therefore, based on the integrated perspective technology, an AKD paper surface treatment agent that uses surface sizing treatment on paper is developed to reduce the application of other additives, and has low cost and simple operation process. At the same time, it improves the water resistance, absorbency and surface strength of paper, which has potential market application value. Summary of the invention

[0007] In order to explain the above technical problem, the first aspect of the present invention provides an integrated paper surface treatment agent based on AKD. The preparation raw materials include the following components by weight: 100-180 parts of AKD wax, 1-46 parts of phase transfer catalyst, 1-45 parts of precious metal nanocatalyst, 300-500 parts of emulsifier, and 800-1100 parts of water.

[0008] As a preferred technical solution of the present invention, the phase transfer catalyst includes at least one of polyether compounds, cyclic crown ether compounds, and quaternary ammonium salt compounds.

[0009] As a preferred technical solution of the present invention, the quaternary ammonium salt compound includes at least one of benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, dodecyldimethylbenzylammonium bromide and N,N-dimethylaminomethylene polyacrylamide.

[0010] As a preferred technical solution of the present invention, the noble metal nanocatalyst includes at least one of nano-gold, nano-silver, nano-platinum, nano-palladium, nano-lanthanum, nano-cerium, and nano-zirconium.

[0011] As a more preferred technical solution of the present invention, the noble metal nanocatalyst is nanogold.

[0012] As a preferred technical solution of the present invention, the nano-gold is water-based spherical nano-gold particles with a particle size of 15-25nm.

[0013] The applicant has found that when AKD emulsion is used as a neutral / alkaline sizing agent for paper, it can significantly improve the water resistance of paper, but it cannot effectively contact the cellulose in the hydrophilic pulp. Excessive AKD emulsion in the system causes poor paper quality, poor printing performance, and poor mechanical properties, which seriously limits the application of AKD emulsion in the field of paper surface treatment agents. In order to solve the above problems, the applicant unexpectedly found that when AKD wax is used as the main raw material, dodecyl dimethyl benzyl ammonium bromide is added to the system as a phase transfer catalyst and nano gold is added as a noble metal nano catalyst, especially when the nano gold is water-based spherical nano gold with a particle size of 15-25nm, the surface strength and mechanical properties of the paper can be enhanced while ensuring that the paper has excellent water resistance. The applicant speculates that the possible reason is that the presence of dodecyldimethylbenzylammonium bromide increases the collision chance between cellulose molecules and AKD molecules in water, provides sufficient conditions for the reaction between cellulose molecules and AKD molecules, and improves the reaction rate of AKD molecules and cellulose molecules. Secondly, aqueous nanogold with a particle size of 15-25nm has excellent compatibility in the system, and produces water-soluble nanogold metal complexes in the system. The presence of the nanogold metal complex can reduce the energy of the LUMO orbit in the AKD molecule, making the AKD molecule easier to react with the cellulose molecules, accelerating the esterification reaction process between the AKD molecules and the cellulose molecules in the pulp system, avoiding the use of acidic catalysts that have a negative effect on paper quality, allowing the AKD molecules in the system to fully react with the pulp, avoiding the phenomenon of excessive presence of AKD leading to a decrease in paper quality, enhancing the surface strength of the paper, and improving the overall quality of the paper.

[0014] As a preferred technical solution of the present invention, the emulsifier includes at least one of sodium lignin sulfonate, corn cationic starch, cassava cationic starch, wheat cationic starch, and potato cationic starch.

[0015] As a more preferred technical solution of the present invention, the emulsifier is sodium lignin sulfonate and corn cationic starch, and the mass ratio of sodium lignin sulfonate to corn cationic starch is (1.5-2.5): (0.2-0.8).

[0016] As a most preferred technical solution of the present invention, the mass ratio of the sodium lignin sulfonate to corn cationic starch is 2.2:0.6.

[0017] As a preferred technical solution of the present invention, the raw materials for preparing the integrated paper surface treatment agent also include a ripening agent and a stabilizer, and the addition amount of the ripening agent and the stabilizer is 25-35% of the addition amount of the AKD wax.

[0018] As a preferred technical solution of the present invention, the aging agent includes at least one of epichlorohydrin-dimethylamine-ethylenediamine copolymer, polydialkyl ammonium halide compounds, and polyacrylamide compounds.

[0019] As a preferred technical solution of the present invention, the viscosity of the epichlorohydrin-dimethylamine-ethylenediamine copolymer is 100-600 cps.

[0020] As a preferred technical solution of the present invention, the stabilizer includes at least one of calcium carbonate, modified cationic starch, polyaziridine, chitin, sodium carboxymethyl cellulose, and chitosan.

[0021] As a more preferred technical solution of the present invention, the stabilizer is calcium carbonate and sodium carboxymethyl cellulose, and the mass ratio of calcium carbonate to sodium carboxymethyl cellulose is (0.3-0.7): (1.1-1.5).

[0022] As a most preferred technical solution of the present invention, the mass ratio of calcium carbonate to sodium carboxymethyl cellulose is 0.5:1.3.

[0023] The second aspect of the present invention provides a method for preparing an integrated paper surface treatment agent based on AKD, comprising the following steps:

[0024] (1) adding AKD wax to the emulsifier and stirring at 20-30° C. for 10-20 min to obtain a mixture A;

[0025] (2) adding water and a phase transfer catalyst to the mixture A described in step (1), stirring and cooling to obtain a mixture B;

[0026] (3) Adding a curing agent, a stabilizer, and a noble metal nanocatalyst to the mixture B described in step (2), and stirring for 70-90 minutes, thereby obtaining the integrated paper surface treatment agent.

[0027] Wherein, the stirring in step (2) is homogenous stirring;

[0028] The stirring temperature in step (2) is 70-80° C. and the stirring time is 80-90 min.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The integrated paper surface treatment agent prepared by the present invention can significantly improve the surface printing strength of the product while ensuring that the paper has excellent water resistance by adding dodecyl dimethyl benzyl ammonium bromide and nano gold as catalysts, especially when the nano gold is water-based spherical nano gold with a particle size of 15-25 nm, and can especially alleviate the phenomenon of paper shedding, powdering and adhesion in areas with air humidity greater than 80%, while shortening the aging time and reducing the cost by 15-20%;

[0031] 2. The integrated paper surface treatment agent prepared by the present invention, by adding sodium lignin sulfonate and corn cationic starch in a mass ratio of 2.2:0.6 into the system, not only improves the compatibility of AKD wax in the pulp system, but also enhances the hydrophobicity of the paper, improves the effect of AKD paper surface treatment in the pulp system, and reduces the amount of additives added by 50% compared with the prior art;

[0032] 3. The integrated paper surface treatment agent prepared by the present invention can interact with other components in the system by adding epichlorohydrin-dimethylamine-ethylenediamine copolymer to the system, thereby ensuring the excellent water resistance of the paper and reducing the environmental protection treatment cost. At the same time, it can completely replace the use of the sizing agent in the pulp, significantly reduce the hydrolysis and loss of AKD, and greatly improve the additive absorption rate of the pulp;

[0033] 4. The integrated paper surface treatment agent prepared by the present invention interacts with other components in the system by adding calcium carbonate and sodium carboxymethyl cellulose in a mass ratio of 0.5:1.3 into the system, thereby improving the stability of AKD and significantly enhancing the surface strength, stiffness and folding resistance of the paper, avoiding the addition of AKD emulsion, surface sizing agent, modifier and reinforcing agent into the system, improving the controllability and yield rate of the surface treatment agent, and reducing the cost of additives;

[0034] 5. The integrated paper surface treatment agent prepared by the present invention does not add too many types of functional additives, which reduces the clogging and pollution of the equipment filter and felt cloth by the additives, prolongs the service life of the forming net and felt cloth, extends the cleaning cycle of the equipment, is suitable for industrial-grade large-scale production, provides a new strategy for the preparation of integrated paper surface treatment agents, and expands the application range of integrated paper surface treatment agents. DETAILED DESCRIPTION

[0035] Example

[0036] Example 1

[0037] Example 1 provides an integrated paper surface treatment agent based on AKD. The preparation raw materials include the following components, by weight: 100 parts of AKD wax, 1 part of phase transfer catalyst, 1 part of precious metal nanocatalyst, 300 parts of emulsifier, 4 parts of curing agent, 4 parts of stabilizer, and 800 parts of water.

[0038] The AKD wax was purchased from Shandong Haoshun Chemical Co., Ltd., model HS-1160;

[0039] The phase transfer catalyst is dodecyl dimethyl benzyl ammonium bromide, and the CAS number of dodecyl dimethyl benzyl ammonium bromide is 7281-04-1;

[0040] The noble metal nanocatalyst is nanogold, purchased from Beijing Zhongke Leiming Technology Co., Ltd., and is water-based spherical nanogold particles with a particle size of 20 nm;

[0041] The emulsifier is sodium lignin sulfonate and corn cationic starch, and the mass ratio of sodium lignin sulfonate to corn cationic starch is 2.2:0.6; the sodium lignin sulfonate is purchased from Shanghai Tingruo Chemical Co., Ltd., and the corn cationic starch is purchased from Nantong Tongdi Biotechnology Co., Ltd.;

[0042] The curing agent is epichlorohydrin-dimethylamine-ethylenediamine copolymer, purchased from Wuxi Lansen Hair Care Co-Products Co., Ltd., model LSC-52, with a viscosity of 200-500cps;

[0043] The stabilizer is calcium carbonate and sodium carboxymethyl cellulose, and the mass ratio of calcium carbonate to sodium carboxymethyl cellulose is 0.5:1.3;

[0044] The CAS number of the calcium carbonate is 471-34-1; sodium carboxymethyl cellulose was purchased from Shanghai Waidian International Trading Co., Ltd., model number CMC2200.

[0045] The preparation method of the integrated paper surface treatment agent based on AKD comprises the following steps:

[0046] (1) adding AKD wax to the emulsifier and stirring at 25° C. for 15 min to obtain a mixture A;

[0047] (2) adding water and a phase transfer catalyst to the mixture A described in step (1), stirring and cooling to obtain a mixture B;

[0048] (3) Adding a curing agent, a stabilizer, and a noble metal nanocatalyst to the mixture B described in step (2), and stirring for 85 minutes, thereby obtaining the integrated paper surface treatment agent.

[0049] Wherein, the stirring in step (2) is homogenous stirring;

[0050] The stirring temperature in step (2) is 75° C. and the stirring time is 85 min.

[0051] Example 2

[0052] Example 2 provides an integrated paper surface treatment agent based on AKD. The preparation raw materials include the following components, by weight: 180 parts of AKD wax, 46 parts of phase transfer catalyst, 45 parts of precious metal nanocatalyst, 500 parts of emulsifier, 6 parts of curing agent, 6 parts of stabilizer, and 1100 parts of water.

[0053] The AKD wax was purchased from Shandong Haoshun Chemical Co., Ltd., model HS-1160;

[0054] The phase transfer catalyst is dodecyl dimethyl benzyl ammonium bromide, and the CAS number of dodecyl dimethyl benzyl ammonium bromide is 7281-04-1;

[0055] The noble metal nanocatalyst is nanogold, purchased from Beijing Zhongke Leiming Technology Co., Ltd., and is water-based spherical nanogold particles with a particle size of 20 nm;

[0056] The emulsifier is sodium lignin sulfonate and corn cationic starch, and the mass ratio of sodium lignin sulfonate to corn cationic starch is 2.2:0.6; the sodium lignin sulfonate is purchased from Shanghai Tingruo Chemical Co., Ltd., and the corn cationic starch is purchased from Nantong Tongdi Biotechnology Co., Ltd.;

[0057] The curing agent is epichlorohydrin-dimethylamine-ethylenediamine copolymer, purchased from Wuxi Lansen Hair Care Co-Products Co., Ltd., model LSC-52, with a viscosity of 200-500cps;

[0058] The stabilizer is calcium carbonate and sodium carboxymethyl cellulose, and the mass ratio of calcium carbonate to sodium carboxymethyl cellulose is 0.5:1.3;

[0059] The CAS number of the calcium carbonate is 471-34-1; sodium carboxymethyl cellulose was purchased from Shanghai Waidian International Trading Co., Ltd., model number CMC2200.

[0060] The preparation method of the AKD-based integrated paper surface treatment agent is the same as that in Example 1.

[0061] Example 3

[0062] Example 3 provides an integrated paper surface treatment agent based on AKD. The preparation raw materials include the following components, by weight: 150 parts of AKD wax, 25 parts of phase transfer catalyst, 10 parts of precious metal nanocatalyst, 400 parts of emulsifier, 5 parts of curing agent, 5 parts of stabilizer, and 1000 parts of water.

[0063] The AKD wax was purchased from Shandong Haoshun Chemical Co., Ltd., model HS-1160;

[0064] The phase transfer catalyst is dodecyl dimethyl benzyl ammonium bromide, and the CAS number of dodecyl dimethyl benzyl ammonium bromide is 7281-04-1;

[0065] The noble metal nanocatalyst is nanogold, purchased from Beijing Zhongke Leiming Technology Co., Ltd., and is water-based spherical nanogold particles with a particle size of 20 nm;

[0066] The emulsifier is sodium lignin sulfonate and corn cationic starch, and the mass ratio of sodium lignin sulfonate to corn cationic starch is 2.2:0.6; the sodium lignin sulfonate is purchased from Shanghai Tingruo Chemical Co., Ltd., and the corn cationic starch is purchased from Nantong Tongdi Biotechnology Co., Ltd.;

[0067] The curing agent is epichlorohydrin-dimethylamine-ethylenediamine copolymer, purchased from Wuxi Lansen Hair Care Co-Products Co., Ltd., model LSC-52, with a viscosity of 200-500cps;

[0068] The stabilizer is calcium carbonate and sodium carboxymethyl cellulose, and the mass ratio of calcium carbonate to sodium carboxymethyl cellulose is 0.5:1.3;

[0069] The CAS number of the calcium carbonate is 471-34-1; sodium carboxymethyl cellulose was purchased from Shanghai Waidian International Trading Co., Ltd., model number CMC2200.

[0070] The preparation method of the AKD-based integrated paper surface treatment agent is the same as that in Example 1.

[0071] Comparative Example 1

[0072] The specific implementation method of Comparative Example 1 is the same as that of Example 3, except that no phase transfer catalyst is added.

[0073] Comparative Example 2

[0074] The specific implementation method of Comparative Example 2 is the same as that of Example 3, except that the particle size of the nano-gold is 50 nm.

[0075] Comparative Example 3

[0076] The specific implementation method of Comparative Example 3 is the same as that of Example 3, except that no noble metal nanocatalyst is added.

[0077] Performance Evaluation

[0078] (1) Absorption performance test:

[0079] 10 kg of the integrated paper surface treatment agent prepared in Examples 1-3 and Comparative Examples 1-3 was tested on a 1500 mm offset paper machine using a paper surface absorption weight meter in accordance with CNS7298-2009 "Cobb Test Method" to test the surface absorption (Cobb value) of the paper. The measured data are shown in Table 1. The smaller the Cobb value, the better the absorption effect on ink.

[0080] The paper surface absorption weight measuring instrument was purchased from Internason Precision Instrument Co., Ltd., model number is HP-XS100.

[0081] (2) Surface strength test:

[0082] The integrated paper surface treatment agent prepared in Examples 1-3 and Comparative Examples 1-3 was subjected to GB / T22837-2008 "Determination of surface strength of paper and paperboard (wax stick method)", and GB / T450-2008 "Taking of paper and paperboard samples and determination of the longitudinal and transverse directions and front and back sides of the samples" was introduced. The surface strength of the paper was measured by destroying the surface of the sample paper through the adhesion force of the wax stick. The measured data are shown in Table 1.

[0083] Table 1

[0084]

[0085]

Claims

1. An integrated paper surface treatment agent based on AKD, characterized in that: The raw materials for preparation include at least the following components by weight: 100-180 parts of AKD wax, 1-46 parts of phase transfer catalyst, 1-45 parts of precious metal nanocatalyst, 300-500 parts of emulsifier, and 800-1100 parts of water; The phase transfer catalyst is dodecyl dimethyl benzyl ammonium bromide; The noble metal nanocatalyst is nanogold; The nano-gold is water-based spherical nano-gold particles with a particle size of 15-25nm; The emulsifiers are sodium lignin sulfonate and corn cationic starch, and the mass ratio of sodium lignin sulfonate to corn cationic starch is (1.5-2.5): (0.2-0.8).

2. The integrated paper surface treatment agent according to claim 1, characterized in that: The raw materials for preparation also include a ripening agent and a stabilizer, and the addition amount of the ripening agent and the stabilizer is 25-35% of the addition amount of the AKD wax.

3. The integrated paper surface treatment agent according to claim 2, characterized in that: The curing agent includes at least one of epichlorohydrin-dimethylamine-ethylenediamine copolymer, polydialkyl ammonium halide compounds, and polyacrylamide compounds.

4. The integrated paper surface treatment agent according to claim 3, characterized in that: The viscosity of the epichlorohydrin-dimethylamine-ethylenediamine copolymer is 100-600 cps.

5. A method for preparing an integrated paper surface treatment agent based on AKD as claimed in any one of claims 2 to 4, characterized in that: The following steps are involved: (1) adding AKD wax to the emulsifier and stirring at 20-30° C. for 10-20 min to obtain a mixture A; (2) adding water and a phase transfer catalyst to the mixture A described in step (1), stirring and cooling to obtain a mixture B; (3) Adding a curing agent, a stabilizer, and a noble metal nanocatalyst to the mixture B described in step (2), and stirring for 70-90 minutes, thereby obtaining the integrated paper surface treatment agent.

Citation Information

Patent Citations

  • Fluorinated acrylate copolymer emulsion paper surface treating agent, preparation method and application thereof

    CN107447593A

  • Preparation method of super-hydrophobic paper surface treating agent

    CN110105500A

  • Alkyl ketene dimer sizing agent and preparation method and application thereof

    AU2020101698A4

  • Paper sizing composition and sizing method

    CA2033265A1